Outcomes following modified extracardiac Fontan procedure of direct total cavopulmonary connection with autologous vessels: a single-centre 10-year experience. (18th November 2019) - Liu, Xiaobing; Yuan, Haiyun; Chen, Jimei; Cen, Jianzheng; Nie, Zhiqiang; Xu, Gang; Wen, Shusheng; Zhuang, Jian
Abstract: : OBJECTIVES: The modified extracardiac Fontan of direct total cavopulmonary connection (dTCPC) with entirely autologous vessels is a better solution in selected patients with functionally univentricular hearts because it combines the advantages of a tubular connection and of full growth potential. We investigated the mid-term to long-term outcomes of the physical condition of patients who had the dTCPC and assessed the growth potential of the autologous dTCPC pathway. METHODS: From July 2005 to June 2014, 31 patients, aged 1.8–14.0 years, underwent a modified extracardiac Fontan with dTCPC at our institution. Twenty-two patients underwent a 1-stage dTCPC and 9 patients underwent a 2-stage dTCPC. The preoperative and postoperative data were reviewed retrospectively. RESULTS: There were 17 (54.8%) boys and 14 (45.2%) girls, with a median age of 6.4 years (range 1.8–14.0 years) and a mean weight of 17.8 kg (range 9–41 kg). The mean follow-up period was 6.0 years (range 2.1–10.2 years). There was 1 early death and 2 late deaths. The event-free survival rate for the 31 patients was 88.9% at 10 years during the follow-up period. Late protein-losing enteropathy, thromboembolism, arrhythmia or heart failure were not observed. There was a significant difference between the preoperative and postoperative data for body mass index and the diameters of the autologous dTCPC pathway and pulmonary artery branches, confirming that the growth potential of the autologous dTCPC pathway was realized. CONCLUSIONS: The dTCPC procedure could be performed with satisfactory midterm to long-term outcomes in selected patients. It has the potential of retaining the advantage of the extracardiac Fontan operation together with the potential for growth and the avoidance of prosthetic materials.